Aspiration biopsy versus dilatation and curettage for endometrial hyperplasia prior to hysterectomy - Woo Yeon Hwang; Dong Hoon Suh; Kidong Kim; Jae Hong No; Yong Beom Kim (BMC, 2021)
Abstract Background To compare the diagnostic accuracy of aspiration biopsy and dilatation and curettage (D&C) in patients diagnosed with endometrial hyperplasia prior to hysterectomy. Methods We retrospectively reviewed medical records of 250 patients diagnosed with endometrial hyperplasia by endometrial sampling between July 2003 and March 2020. Endometrial sampling was performed by aspiration biopsy (n = 150) or D&C (n = 100), followed by hysterectomy within 6 months. Pathological findings of hysterectomy specimens of the two groups were compared to preoperative findings. Results The overall diagnostic concordance between endometrial sampling specimen including D&C and aspiration biopsy, and hysterectomy specimen was 51.0% (51/100) and 41.3% (62/150), respectively. Patients whose preoperative specimen was obtained by D&C were upgraded less significantly than those who underwent aspiration biopsy (21.0% vs 36.7%; P = 0.008). In particular, significantly fewer patients were upgraded after D&C than after aspiration biopsy in hyperplasia without atypia (12.5% vs 29.0%; P = 0.028). In addition, when the final pathological upgrade rate to endometrial carcinoma was evaluated between the two methods of endometrial sampling, significantly fewer cases were noted after D&C than after aspiration biopsy (15.0% vs 27.3%; P = 0.022). Conclusions In our study, D&C more accurately reflected the final diagnosis in patients with endometrial hyperplasia than aspiration biopsy based on the histological examination of hysterectomy specimens. When considering the management strategy for women with an endometrial hyperplasia diagnosis obtained by aspiration biopsy, physicians should consider the significant rate of upgraded diseases with this method of endometrial sampling.